2013
DOI: 10.1371/journal.pone.0070158
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-1 Downregulation Increases Connexin 43 Displacement and Induces Ventricular Tachyarrhythmias in Rodent Hypertrophic Hearts

Abstract: Downregulation of the muscle-specific microRNA-1 (miR-1) mediates the induction of pathologic cardiac hypertrophy. Dysfunction of the gap junction protein connexin 43 (Cx43), an established miR-1 target, during cardiac hypertrophy leads to ventricular tachyarrhythmias (VT). However, it is still unknown whether miR-1 and Cx43 are interconnected in the pro-arrhythmic context of hypertrophy. Thus, in this study we investigated whether a reduction in the extent of cardiac hypertrophy could limit the pathological e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
44
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 70 publications
(47 citation statements)
references
References 55 publications
2
44
0
1
Order By: Relevance
“…Patients with coronary artery disease [199] Hypertrophic cardiac muscle Cx43 increased miR-1 targets Cx43 Downregulation of miR-1 mediates induction of pathologic cardiac hypertrophy Hypertrophic rat cardiomyocytes in vitro and in vivo [200] Cx43 downregulated miR-1 targets Cx43 Cx43 protein downregulated in miR-1 Tg mice compared to WT mice…”
Section: Klf15mentioning
confidence: 99%
“…Patients with coronary artery disease [199] Hypertrophic cardiac muscle Cx43 increased miR-1 targets Cx43 Downregulation of miR-1 mediates induction of pathologic cardiac hypertrophy Hypertrophic rat cardiomyocytes in vitro and in vivo [200] Cx43 downregulated miR-1 targets Cx43 Cx43 protein downregulated in miR-1 Tg mice compared to WT mice…”
Section: Klf15mentioning
confidence: 99%
“…4 Evidences from both experimental and clinical studies have shown that miRs play a key role in the regulation of several aspects of cardiovascular diseases. [5][6][7][8][9][10] MicroRNAs are interesting because they have both a powerful and fine regulatory function. In fact, a single miR can modulate the expression of several genes, and multiple miRs can target the same gene as well as interact with each other to form miR-miR cotargeting networks, thus making their regulatory potential even larger.…”
Section: Micrornas and Their Biogenesismentioning
confidence: 99%
“…With respect to adaptive growth regulation, miRs have been identified and associated with several cardiovascular diseases, including neointimal proliferation after vascular injury (7,8), ischemic cardiomyo pathy (9), and cardiac hypertrophy (10)(11)(12)(13)(14). The importance of miRs in cardiovascular biology has also been demonstrated in animals with conditional deletion of the essential miRprocessing enzyme dicer1.…”
mentioning
confidence: 99%